UPAYA MENINGKATKAN KECERDASAN NATURALIS ANAK USIA 5-6 TAHUN MELALUI METODE KARYAWISATA - Putri Clawson; Zulafni (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2018)
This study aims to determine whether the naturalist intelligence of children aged 5-6 in TK Ikhlas Bukit Raya Pekanbaru can be improved through the field trip method. The method used in this research is Classroom Action Research with a total of 20 research subjects consisting of 9 boys and 11 girls. Data collection techniques data collection in this study is observation and documentation. The data analysis technique used in this study is the percentage technique. The results of research conducted, through the method of tourism work can improve the naturalist intelligence of Children aged 4-5 years at TK Ikhlas Bukit Raya Pekanbaru Kindergarten. Naturalist intelligence in children in TK Ikhlas Bukit Raya Pekanbaru from cycle I to cycle II. in cycle I obtained an average score of 37.6 (45.7%) with kiteria starting to develop. There was an increase in naturalist intelligence increase in children in TK Ikhlas Bukit Raya Pekanbaru in cycle II with an average score of 64.5 (80.6%) with very well developed criteria (BSB). And it was concluded that the field trip method could improve the naturalist intelligence of children aged 5-6 in the Amal Ikhlas Bukit Raya Kindergarten, Pekanbaru.